A new class of closed-cell aluminium foams reinforced with carbon nanotubes - Duarte, I.
This manuscript reports on the fabrication of closed-cell aluminium alloy foams reinforced with carbon nanotubes (CNTs) through a novel approach that combines the powder metallurgy method with colloidal processing step that grants uniform dispersion of CNTs into the aqueous suspension of all powder components. Spraying the as prepared suspension into liquid nitrogen followed by lyophilisation enables obtaining homogeneous spherical granules to be used in the powder metallurgy method. Besides ensuring good dispersion of all powder components in the system, the non-agglomerated form of CNTs and the expansion upon foaming foster their structural integrity under stretched conditions in the final foams for an efficient load transfer.